2021
DOI: 10.2147/ijgm.s298586
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus Infection Among Patients Attending at Addis Alem Primary Hospital, Bahir Dar, Northwest Ethiopia

Abstract: Background: Hepatitis B virus (HBV) causes severe liver disease, such as hepatocellular carcinoma (HCC) and life-threatening liver disease. Hepatitis B virus infection is one of the most dominant public health problems these days. Therefore, this study aimed to determine the seroprevalence of HBV infection among patients attending

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
2
1
Order By: Relevance
“…A cross-sectional study in Tanzania also reported consistent HBV infection rates among pregnant women [ 33 ]. Some other research findings in Ethiopia and abroad revealed that the seroprevalence of HBV among the same study subjects was lower than that of the current study [ 6 , 13 , 19 , 20 , 34 ]. On the contrary, some other studies showed higher HBV infection rate among different population groups and among pregnant mothers.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…A cross-sectional study in Tanzania also reported consistent HBV infection rates among pregnant women [ 33 ]. Some other research findings in Ethiopia and abroad revealed that the seroprevalence of HBV among the same study subjects was lower than that of the current study [ 6 , 13 , 19 , 20 , 34 ]. On the contrary, some other studies showed higher HBV infection rate among different population groups and among pregnant mothers.…”
Section: Discussioncontrasting
confidence: 76%
“…In some situations, even pregnant women may not be aware of their HBV serostatus [22], and only a few of the study participants had knowledge about HCV and HBV [23]. The two viral hepatitis seroprevalences among pregnant women become increased through the course of time in different localities of Ethiopia and various parts of Africa [6,[23][24][25][26]. On the contrary, viral hepatitis showed a decreasing pattern in certain developed countries like China [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is in agreement with studies conducted in Ghana on blood donors, revealing that the highest seroprevalence was among the 30-39 years age group 8.9% (45). However, our study is not in agreement where the highest prevalence was recorded among the age group between 21-30 years 48 (2.4%) (25).…”
Section: Discussionsupporting
confidence: 82%